Islamic Equity Financing as an Alternative of Capital Structure to Improve Business Performance: A Systematic Literature Review - Wicaksono, Rianto Anugerah; Syihabuddin, Atok; Salleh, Ahmad Dahlan; Huda, Bakhrul (El-Qist: Journal of Islamic Economics and Business (JIEB), 2024)
This study presents a systematic literature review of capital structure choices with a particular focus on Islamic equity financing and its impact on business performance. By synthesizing 172 Scopus-indexed articles from 1999 to 2023, the research examines the comparative dynamics of internal financing, trade credit, debt financing, and equity financing—including the Islamic mode of mushārakah. Key theoretical frameworks, namely the Pecking Order Theory and Trade-Off Theory, are used to analyze how firms navigate capital structure decisions amid considerations such as cost, control, risk, and tax implications. The findings demonstrate a growing academic and practical interest in Islamic equity financing as a profit-and-loss sharing alternative that aligns with ethical finance principles. However, challenges remain in its adoption due to risk asymmetry and limited regulatory and institutional support. This review further highlights technological innovations—such as blockchain and big data analytics—as emerging solutions to mitigate risk and information asymmetry in Islamic equity models. The specific contribution of this study to the international research field lies in its comprehensive mapping of the development and application of mushārakah-based financing across various contexts and sectors, offering a unique cross-comparison with conventional equity models. It contributes to global discourse by positioning Islamic equity financing not merely as a faith-based solution, but as a viable, ethical, and technologically adaptive alternative to conventional financing models. The study opens new research directions for scholars and practitioners in Islamic finance, fintech, and capital structure optimization.